2021
DOI: 10.2144/fsoa-2020-0190
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Neuroendocrine Tumor and Diabetes Mellitus on Patient Outcomes and Care: a Matched case–control Study

Abstract: Aim: We aimed to determine the impact of diabetes mellitus (DM) on survival of patients with neuroendocrine tumors (NETs) and of NETs on glycemic control. Patients & methods: Patients with newly diagnosed NETs with/without DM were matched 1:1 by age, sex and diagnosis year (2005–2017), and survival compared (Kaplan–Meier and Cox proportional hazards). Mixed models compared hemoglobin A1c (HbA1c) and glucose during the year after cancer diagnosis. Results: Three-year overall survival was 72% (95% CI: 60–86%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In their case-control study, diabetes had no negative impact on the survival of patients with neuroendocrine tumors [41]. Similarly, Pusceddu et al have not recognized diabetes as a negative prognostic factor [39].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In their case-control study, diabetes had no negative impact on the survival of patients with neuroendocrine tumors [41]. Similarly, Pusceddu et al have not recognized diabetes as a negative prognostic factor [39].…”
Section: Discussionmentioning
confidence: 88%
“…Tan et al reported that preoperative new-onset diabetes and impaired fasting glucose (IFG) are correlated with aggressive tumor behavior and poor recurrence-free survival (RFS) of patients with non-functional PanNENs [ 40 ]. Different conclusions were drawn from study by Kusne et al In their case–control study, diabetes had no negative impact on the survival of patients with neuroendocrine tumors [ 41 ]. Similarly, Pusceddu et al have not recognized diabetes as a negative prognostic factor [ 39 ].…”
Section: Discussionmentioning
confidence: 92%
“…However, for more advanced diseases, biotherapy using somatostatin analogs may be used [18]. Somatostatin analogs may inhibit the secretion of insulin and glucagon, thus impacting glycemic balance [3]. Everolimus has also been used as a therapeutic agent both alone and in combination with the somatostatin analog, octreotide, and has been associated with hyperglycemia [19].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoid tumors themselves, as well as certain existing treatments, can impact the management of other conditions, such as diabetes, by impacting glycemic control and balance [2]. Given that the incidences of neuroendocrine tumors, diabetes, and hypertension are rising [3,4], better elucidating the impact of carcinoid tumors and their treatments on such conditions, as well as formally establishing treatment protocols to optimize patient counseling is important. Patients also should be regularly counseled on screening recommendations that may enable earlier diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of therapies for NENs, such as somatostatin analogues (SSAs) and mTOR inhibitors, can also cause impaired glucose metabolism and insulin resistance [100]. Diabetes is an established risk factor for NENs, although most evidence suggests that patients with NENs and diabetes generally do not differ significantly in their outcomes in comparison to non-diabetic patients [100,101]. However, some studies have suggested that diabetes can modify the risk of metastases.…”
Section: Diabetes Obesity and Nensmentioning
confidence: 99%